The effect of capital structure, liquidity, activity ratio, and profitability on the value of pharmaceutical companies - Firnandes, Firnandes; Suhardi, Suhardi; Adriana, Nana (International Enterprise Integration Association, 2025)
This study aims to investigate the impact of capital structure, liquidity, activity ratio, and profitability on firm value in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2023. A quantitative approach was employed using multiple linear regression analysis to analyze panel data from 10 pharmaceutical companies, resulting in a total of 60 observations (n = 60). The results of the regression analysis indicate that only capital structure has a significant effect on firm value. In contrast, liquidity, activity ratio, and profitability do not show a significant impact. These findings were influenced by the dynamics of the capital market during the study period, particularly the effects of the COVID-19 pandemic, which altered investors' strategies and priorities. The results highlight the importance of adopting a more comprehensive approach in evaluating firm value within the pharmaceutical industry by incorporating external factors and additional financial metrics. Future research is recommended to include macroeconomic variables and industry policies to gain a more holistic understanding.